Evaluation of the Psychometric Properties of the Health Assessment Questionnaire (HAQ) in a Population of Individuals With Multiple Sclerosis - Berardi, Anna; Conte, Antonella; Cimmino, Lucilla; Cimmino, Carlotta; Baione, Viola; Crisafulli, Sebastiano Giuseppe; Tofani, Marco; Tartaglia, Matteo; Fabbrini, Giovanni; Galeoto, Giovanni (Frontiers in Neurology, 2022)
Introduction: The Health Assessment Questionnaire (HAQ) has been translated into many languages and it has been classified as the predictor of disability and medical costs, however, the psychometric properties of the HAQ have never been studied in a population with neurological disease. The purpose of this study was the evaluation of the psychometric properties of HAQ in a population of individuals with Multiple Sclerosis (MS). Material and Methods: This cross-sectional study was conducted with patients diagnosed with MS. The evaluation tools administered were the SF-36, to evaluate the health state of the patients, and HAQ, to evaluate the limitations of the activities of daily living (ADL). Results: A total of 34 patients were included in this study. Cronbach’s alpha assessed the internal consistency of the HAQ, and it is equal to 0.94. The study revealed some significant correlations between the dimensions of the SF-36 and the sub-categories of the HAQ using the Pearson’s Correlation Coefficient. Significant correlations emerged between the demographic and clinical characteristics of patients and the subcategories of HAQ. Discussion: HAQ is a valid and reliable tool to assess the limitations of the activities of daily living and it could provide for the healthcare and rehabilitation sector with an additional evaluation tool.